2013
DOI: 10.1002/grl.50802
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis between coral reef calcification and the seawater aragonite saturation state

Abstract: [1] Some predictions of how ocean acidification (OA) will affect coral reefs assume a linear functional relationship between the ambient seawater aragonite saturation state (Ω a ) and net ecosystem calcification (NEC). We quantified NEC in a healthy coral reef lagoon in the Great Barrier Reef during different times of the day. Our observations revealed a diel hysteresis pattern in the NEC versus Ω a relationship, with peak NEC rates occurring before the Ω a peak and relatively steady nighttime NEC in spite of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
78
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 24 publications
18
78
2
Order By: Relevance
“…Short term BEAMS measurements demonstrated that NCC and NCP were tightly coupled over multiple days (Figure 3B), which is consistent with previous observations from various coral reefs (McMahon et al, 2013;Albright et al, 2015;Shaw et al, 2015;Takeshita et al, 2016). The NCC:NCP based on a model II regression between the two parameters was 0.21 ± 0.01, though this ratio calculated from O 2 and pH measurements is dependent on the assumed Q, and varies between 0.08 and 0.33 when Q is set equal to 0.9 and 1.1, respectively (Figure 3).…”
Section: Benthic Metabolic Ratessupporting
confidence: 91%
See 1 more Smart Citation
“…Short term BEAMS measurements demonstrated that NCC and NCP were tightly coupled over multiple days (Figure 3B), which is consistent with previous observations from various coral reefs (McMahon et al, 2013;Albright et al, 2015;Shaw et al, 2015;Takeshita et al, 2016). The NCC:NCP based on a model II regression between the two parameters was 0.21 ± 0.01, though this ratio calculated from O 2 and pH measurements is dependent on the assumed Q, and varies between 0.08 and 0.33 when Q is set equal to 0.9 and 1.1, respectively (Figure 3).…”
Section: Benthic Metabolic Ratessupporting
confidence: 91%
“…Second, the magnitude of variability (but not the TA-DIC slope) is dependent on water depth and flow rates, as shallower depth and slower flow rates will allow for larger accumulation of chemical signatures. This has been well characterized and observed on reef flat environments (Shaw et al, 2012;McMahon et al, 2013;Kwiatkowski et al, 2016). A larger range in TA and DIC will lead to more robust linear regression results, and thus lower uncertainty in NCC:NCP.…”
Section: Spatial Variabilitymentioning
confidence: 64%
“…Unfortunately, instrument failures during this pilot study prevented us from making the high-precision, high-throughput carbon system measurements (TA and DIC) necessary to employ control volume approaches toward estimating NCC and NCP (Falter et al 2008;Teneva et al 2013). Although we were able to provide upper bound estimates on NCC and NCP across the reef flat, it is hard to extrapolate these metabolic rates to broader conclusions about long-term carbon fluxes on the reef given that previous studies have demonstrated NCC and NCP variability over the course of a diel cycle and between consecutive days (McMahon et al 2013;Koweek et al 2015). Unfortunately, the longer-term hydrodynamic measurements in Pool 300, while potentially suitable for continuous estimates of transport across the reef flat, occurred after the high-resolution study in Pool 100 and without biogeochemical measurements, precluding direct estimates of NCC and NCP there as well.…”
Section: Discussionmentioning
confidence: 85%
“…The island is 800 m long,~300 m wide, and 3 m above sea level. Heron Island is surrounded by a lagoonal coral reef, which covers an area of~27 km 2 with an average depth of 1.7 m [McMahon et al, 2013]. The sediments consist primarily of calcareous skeletal matter from reef organisms.…”
Section: Methodsmentioning
confidence: 99%